Bunga Matahari Sebagai Ide Penciptaan Karya Tekstil dengan Teknik Makrame - Devyana Devyana; Eliya Pebriyeni (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The purpose of making this final work is to create and introduce creative ideas for textile crafts using macrame techniques as the completion of the final work. Then introduce the general public to what macrame is, and later it will be taught as a display idea in the room which has the function of decorating mirrors. The methods used in making this final work are the preparation stage, elaboration stage, synthesis stage, concept realization stage, and completion stage. Based on the method that has been carried out, seven sunflower works have been realized as ideas for creating textile works using macrame techniques with the following work titles: first work,